Labor Market Institutions : A Review of the Literature - Betcherman, Gordon (World Bank, Washington, D.C., 2013)
This paper reviews the findings of more than 150 studies on the impacts of four types of labor market institutions: minimum wages, employment protection regulation, unions and collective bargaining, and mandated benefits. The review places particular emphasis on results from developing countries. Impacts studied are on living standards (employment and earnings effects), productivity, and social cohesion, to the extent that this has been analyzed. Strong and opposing views are held on the costs and benefits of labor market institutions. On balance, the results of this review suggest that, in most cases, the impacts of these institutions are smaller than the heat of the debates would suggest. Efficiency effects of labor market regulations and collective bargaining are sometimes found but not always, and the effects can be in either direction and are usually modest. Distributional impacts are clearer, with two effects predominating: an equalizing effect among covered workers but groups such as youth, women, and the less skilled disproportionately outside the coverage and its benefits. While the overall conclusion is one of modest effects in most cases, this does not mean that impacts cannot be more dramatic where regulations are set or institutions operate in ways that exacerbate the labor market imperfections that they were designed to address.